Optimizing Building-Integrated Renewable Energy Systems (BIRES) For Climate and Environmental Security in South-East Nigeria (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
The built environment in South-East Nigeria presents significant opportunities for advancing climate action through building-integrated renewable energy systems (BIRES). This study examined the optimization of BIRES for climate and environmental security among builders and civil engineers in Abia, Anambra, Ebonyi, Enugu, and Imo States. Using a cross-sectional survey design, data were collected from 150 registered professionals selected through stratified random sampling. Findings revealed low BIRES adoption and optimization awareness, with major barriers including lack of tropical climate design guidelines, absence of building code requirements, inadequate technical capacity, limited government incentives, and the high cost of imported components. Despite limited optimization practices, respondents strongly acknowledged the climate and environmental security benefits of BIRES, particularly in reducing greenhouse gas emissions, improving energy resilience, and enhancing sustainable building performance. Two-way ANOVA analysis showed that professionals with higher optimization awareness reported significantly greater perceptions of climate security benefits, while those lacking lifecycle optimization practices perceived higher environmental security risks. Both hypotheses were not accepted at p < 0.001. The study concludes that inadequate optimization knowledge and limited lifecycle practices hinder the effective contribution of BIRES to sustainable energy and environmental security. It recommends mandatory professional training on BIRES optimization, stronger institutional support, financial incentives, and the integration of lifecycle assessment standards into regional building regulations and professional practice frameworks.